Vascular endothelial growth factor-A165b ameliorates outer-retinal barrier and vascular dysfunction in the diabetic retina - Ved, Nikita; Hulse, Richard P.; Bestall, Samuel M.; Donaldson, Lucy F.; Bainbridge, James W.; Bates, David O. (Portland Press, 2017)
Diabetic retinopathy (DR) is one of the leading causes of blindness in the developed world. Characteristic features of DR are retinal neurodegeneration, pathological angiogenesis and breakdown of both the inner and outer retinal barriers of the retinal vasculature and RPE-choroid respectively. Vascular endothelial growth factor-A (VEGF), a key regulator of angiogenesis and permeability, is the target of most pharmacological interventions of DR. VEGF-A can be alternatively spliced at exon 8 to form 2 families of isoforms, pro- and anti-angiogenic. VEGF-A165a is the most abundant pro-angiogenic isoform, is pro-inflammatory and a potent inducer of permeability. VEGF-A165b is anti-angiogenic, anti-inflammatory, cytoprotective and neuroprotective. In the diabetic eye, pro-angiogenic VEGF-A isoforms are up-regulated such that they overpower VEGF-A165b. We hypothesized that this imbalance may contribute to increased breakdown of the retinal barriers and by redressing this imbalance, the pathological angiogenesis, fluid extravasation and retinal neurodegeneration could be ameliorated. VEGF-A165b prevented VEGF-A165a and hyperglycaemia-induced tight junction breakdown and subsequent increase in solute flux in RPE cells. In streptozotocin-induced diabetes, there was an increase in Evans’ blue extravasation after both 1 and 8 weeks of diabetes, which was reduced upon intravitreal and systemic delivery of rhVEGF-A165b. 8-weeks diabetic rats also showed an increase in retinal vessel density, which was prevented by VEGF-A165b. These results show rhVEGF-A165b reduce DR-associated BRB dysfunction, angiogenesis and neurodegeneration and may be a suitable therapeutic in treating DR.